Zerwania i ślady. O kryzysie krytyki literackiej raz jeszcze (z krakowską szkołą krytyki literackiej w tle) - Muca, Klaudia (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article introduces the issue of a crisis of literary criticism in Poland in the 20th and 21st centuries. The crisis is linked to the spheres of culture described by the term literacy (or cultural literacy). One of the reasons for the crisis is the series of ruptures in the tradition of literary criticism. In order to overcome this crisis, it is crucial to relate the ruptured threads of narration on literary criticism. The Krakow school of literary criticism serves here as an example of a rupture between the present and the tradition (or heritage). Another problem analysed in the text is that of establishing a tradition and a school of thought. By verifying some of the elements of the discourse on literary criticism (e.g. Masters, ruptures, traces, melancholic position), some possibilities for overcoming the crisis are being considered.